2000
DOI: 10.1099/00221287-146-8-2027
|View full text |Cite
|
Sign up to set email alerts
|

Genomic subpopulations within the species Pediococcus acidilactici detected by multilocus typing analysis: relationships between pediocin AcH/PA-1 producing and non-producing strains The GenBank accession numbers for the sequences determined in this work are given in Table 4 T4 .

Abstract: A high degree of genetic polymorphism among P. acidilactici strains was highlighted by a multilocus typing approach analysing several housekeeping genes and by sampling the whole genome using random amplified polymorphic DNA (RAPD) fingerprint analysis performed by using a single primer pedA gene targeted in low-stringency amplification conditions. Restriction fragment length polymorphism of the rpoC, ldhD/L and mle genes, and a modified RAPD analysis, permitted the grouping of Pediococcus acidilactici strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…4A, lanes 4 to 7) sharing DNA fragments of approximately 80, 130, and 170 kb. Therefore, both approaches suggest that the species can be divided into at least two genotypic groups and this diversity within the species is in agreement with recent studies (29,30). Interestingly, two P. pentosaceus strains, NCIMB 8127 and NCIMB 8952, which shared the P. acidilactici PFGE patterns for NotI (Fig.…”
Section: Vol 68 2002 Rapd Pcr and Pfge Analysis Of Pediococci 767supporting
confidence: 75%
See 2 more Smart Citations
“…4A, lanes 4 to 7) sharing DNA fragments of approximately 80, 130, and 170 kb. Therefore, both approaches suggest that the species can be divided into at least two genotypic groups and this diversity within the species is in agreement with recent studies (29,30). Interestingly, two P. pentosaceus strains, NCIMB 8127 and NCIMB 8952, which shared the P. acidilactici PFGE patterns for NotI (Fig.…”
Section: Vol 68 2002 Rapd Pcr and Pfge Analysis Of Pediococci 767supporting
confidence: 75%
“…To date, RAPD PCR studies of pediococci have been based on single random primers. An 18-mer primer originally designed to target a pediocin-encoding gene on a plasmid from P. acidilactici was only effective at discriminating strains of P. acidilactici, with 19 strains producing seven distinct RAPD patterns (29,30). In another study, a 17-mer primer discriminated nine pediococci isolated from the gastrointestinal tracts of ducks into four groups and partial 16S ribosomal sequencing indicated that each group represented a single species (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…New techniques could be used to analyze such variants, such as multilocus typing, which analyzes several housekeeping genes involved in transcriptional or translational cell machinery, to highlight a high degree of genetic polymorphisms among strains of a species (22). In this study, the growth characteristics of the two variants in different types of milk and during yogurt production were indistinguishable from those of the wild-type strain (data not shown).…”
Section: Discussionmentioning
confidence: 70%
“…1). Identification to species level is best obtained by 16S rDNA gene sequencing Kurzak et al, 1998;Omar et al, 2000;Barney et al, 2001), species-specific DNA probes (Lonvaud-Funel et al, 1993;Mora et al, 1997;Rodrigues et al, 1997), ribotyping (Jager & Harlander, 1992;Satokari et al, 2000;Barney et al, 2001;Santos et al, 2005), randomly amplified polymorphic DNA (RAPD) PCR (Kurzak et al, 1998;Nigatu et al, 1998;Mora et al, 2000;Simpson et al, 2002;Fujii et al, 2005;Tamang et al, 2005), and pulsed-field gel electrophoresis (PFGE) ( Dellaglio et al, 1981;Luchansky et al, 1992;Barros et al, 2001). Simpson et al (2006) developed a rapid PFGE protocol for species-and strain-level differentiation.…”
Section: The Genus Pediococcusmentioning
confidence: 99%